(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2022)
Synthesis of KZnF\(_3\) is rather tedious. Typical problems of fluoride synthesis are faced with more acuteness. Even in wet chemical preparations, use of hygroscopic starting materials like zinc chloride or nitrate presents considerable difficulties. A simple precipitation synthesis of KZnF\(_3\) with aqueous solutions of zinc sulfate and potassium fluoride is described. Precipitation at the room temperature produces the compound profoundly contaminated with hydroxide phase. Phase pure compound is obtained when boiling solutions are mixed. Activators Cerium and europium could be incorporated by adding the corresponding sulfates to zinc sulfate solution during the precipitation. As prepared phosphor exhibited typical Ce\(^3+\) luminescence. For obtaining Eu\(^2+\) luminescence, the phosphor had to be given reducing treatment.